Bristle motion, forces, and related vertical translation for a novel electric toothbrush design - Goldschmidtboeing, Frank (Strojniški vestnik, 2020)
This paper presents a combination of theoretical and experimental techniques applied to characterize the bristle motion, forces, and related vertical translation for a novel electric toothbrush design with a linear drive system. Results of the theoretical description, based on a single filament, were successfully compared with laboratory-based investigations: force measurements and high-speed video analysis, and tracking the toothbrush motion. This work describes the vertical translation induced in the toothbrush head, of up to 250 microm, when the toothbrush bristles are applied against a contact surface at brushing loads of approximately 1 N to 2.5 N. Using these techniques, including Fast-Fourier transform analysis, it is shown that the vertical motion of the head is composed of the driving frequency and its harmonics.
Keywords: bristle forces; bristle motion; electric toothbrush; električna zobna ščetka; gibanje ščetin; inclined toothbrush filaments; poševna vlakna zobne ščetke; sile ščetin; single filament theory; teorija posameznih vlaken